Sediment Characteristic of Pagai Strait, Mentawai - Mutmainah, Herdiana; Kusumawardani, Rini (Semarang State University, 2019)
Abstract. The marine sediment is important indicator of the seafloor. The characteristics of marine sediments can be seen from grain size, type and Total Dissolved Solid (TDS). Sediments derived from organic and non-organic particles are carried by the sea currents, waves, streams and tidal process in the coastal areas. At very high levels, sediments can cause pollution or vulnerability such as decreasing of dissolved oxygen, coral bleaching, and increased the eurotrification processes. Pagai Strait is located between North Pagai Island and South Pagai. This strait has enormous potential and it is used by the surrounding community for various activities such as port and sea transportation, fishery, marine aquaculture and tourism. This study aims to determine the characteristics of sediment in Pagai Strait. The field survey was conducted in September 2016 for waves, currents, water quality and sediment samples with purposive sampling method. The results showed that the average of sediments in Pagai Strait is D35 sized 0.155 mm; D50 sized 0.273 mm; and D90 sized 1.574 mm with specific gravity 2.665 gr/cm3 and dominated by sand 66.88%. TDS between 51.6 to 55.0 mg/L, appropriate for port and mangrove. Scale of sediment, A = 0.119 and sediment velocity is 0.002 m/s. Sediment transport approximately is 0.389 m3/day.